Compliance Audit of Processed Complementary Foods in Urban Ghana - Aryeetey, Richmond Nii Okai; Tay, Marcella (Frontiers in Public Health, 2015)
Background and objectives: Although Processed Complementary Foods (PCF) can contribute to meeting dietary needs of infants and young children, it has been associated with unethical marketing practices which undermine practice of exclusive breastfeeding for six months. The current study assessed PCF labeling compliance to the International Code of marketing of Breast Milk Substitutes (CMBMS), and the National Breastfeeding Promotion Regulation (NBPR), in Ghana. Methods: A variety of PCF were purchased from child welfare clinics, fuel station shops, supermarkets, ‘mother/baby’ care shops and pharmacies in the La and Osu Klottey sub-metropolitan areas in Accra. The labels were evaluated against best practice indicators proposed by the Maternal Infant and Young Child Nutrition (MIYCN) Working Group based on the international CMBMS, and also indicators based on the NBPR. An overall compliance estimate was determined based on intensity of compliance to the indicators. Results: The PCF purchased included cereal-based products, fruit juices, fruit and vegetable purees, milk-based products, and combination meals; seventy-five percent of PCF were imported. One hundred of the 108 products identified were labeled in English and thus included in analysis. None of the products complied with all labeling requirements of CMBMS or NBPR; 84% and 17% of product labels complied with at least 50% of NBPR and 50% of CMBMS indicators, respectively. Only 5% of labels had content indicating importance of exclusive breastfeeding for 6 months. Additionally, only 5% of labels warned against the hazard of introducing PCF earlier than 6 months as required by the NBPR. Conclusions: Labeling of most PCF sold by selected retailers in Accra did not comply with NBPR and CMBMS labelling requirements. Enforcement of local law on labeling of PCF is urgently needed.